Frequency-dependent conductivity in As0.40Se0.40Te0.20 thin films - (:unkn) unknown (ELSEVIER SCIENCE SA LAUSANNE, 1996)
D.c. and a.c. conductance measurements were performed on As0.40Se0.40Te0.20 thin films. The d.c. measurements were performed at temperatures between 100 and 400 K. The a.c. measurements were performed at temperatures between 148 and 403 K and at frequencies between 12.2 kHz and 2.5 MHz. The d.c. measurements indicate two types of conduction mechanisms, which are interpreted as band-to-band conduction above 235 K and localized state conduction below that. A.c. conductivity of the films is well represented by the form A omega s where A and s are found to be temperature-dependent parameters. The data are found to fit the correlated barrier hopping (CBH) model, especially at low temperatures. The a.c. data show a perfect agreement with the quasi-universal law predicted by the extended pair approximation (EPA) calculations. Using the EPA value for CBH the decay parameter of the wavefunction was calculated to be 15.1 Angstrom, which is close to the theoretically assumed value of around 10 Angstrom.
Keywords: amorphous materials; chalcogens; conductivity; electrical properties and measurements; DC HOPPING CONDUCTIVITY; AMORPHOUS-SILICON FILMS; AC CONDUCTIVITY; CHALCOGENIDE GLASSES; SEMICONDUCTORS